From Italy with Rage: Feminists Striking in Uncertain Times - Salvatori, Lidia (Atlantis)

(untitled) (Mount Saint Vincent University, 2023)
In this contribution, I reflect on the significance of the Paro Internacional de Mujeres (International Women’s Strike) for contemporary Italian feminism. I draw from autoethnographic research within the feminist movement Non Una di Meno (Not One Less) to explore how the organization of the strike on March 8, 2017, contributed to the development of the movement's theorization and mobilization strategies. In this piece, I illustrate how digital connectivity had a central role in facilitating the expression of solidarity and processes of exchange and ‘contamination’ (Salvatori 2021) between movements across borders. I describe how the sharing of materials, slogans, hashtags, and songs centred on similar claims contributed to the construction of a transnational political subject. Through the strike, feminists analyzed and denounced how economic and patriarchal violence play out in the context of Italy, while highlighting the systemic and non-exceptional character of these forces within neoliberal societies more broadly.